2008
DOI: 10.1159/000121070
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cytogenetics of forest trees

Abstract: The economic and ecological importance of forest trees, as well as their unique biological features, has recently raised the level of interest in studies on their genomes, including sequencing of the entire poplar genome. However, cytogenetic studies have not moved in parallel with developments in genomics. This is especially true for hardwood species characterized by small genomes and relatively high numbers of small chromosomes. Molecular cytogenetic studies have mainly been focused on coniferous species, ow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
13
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 139 publications
2
13
0
Order By: Relevance
“…We observed that the 5S rDNA FISH signal in P. trichocarpa is much reduced compared to either of the 18S-28S rDNA signals, apparently because the 5S rDNA locus contains fewer repetitive units than either of the 18S-28S rDNA loci. Similar results were also reported for P. nigra [Ribeiro et al, 2008].…”
Section: Discussionsupporting
confidence: 90%
“…We observed that the 5S rDNA FISH signal in P. trichocarpa is much reduced compared to either of the 18S-28S rDNA signals, apparently because the 5S rDNA locus contains fewer repetitive units than either of the 18S-28S rDNA loci. Similar results were also reported for P. nigra [Ribeiro et al, 2008].…”
Section: Discussionsupporting
confidence: 90%
“…FISH‐based karyotyping relies on chromosome markers, which are independent of genetic diversity, and may complement genetic mapping in studies of chromosome organization and evolution. Chromosome identification systems employing FISH have been used to construct karyotypes or cytogenetic maps in rice ( Oryza sativa ), Sorghum bicolor , maize ( Zea mays ), Antirrhinum majus , poplar ( Populus alba ), common bean ( Phaseolus vulgaris ), soybean ( Glycine max ), melon ( Cucumis melo ) and Brassica napus (Cheng et al ., ; Islam‐Faridi et al ., ; Kato et al ., ; Zhang et al ., ; Ribeiro et al ., ; Pedrosa‐Harand et al ., ; Findley et al ., ; Fonseca et al ., ; Liu et al ., ; Pires & Xiong, ). Large genomic clones, such as bacterial artificial chromosomes (BACs), provide reliable landmarks with which to discriminate individual chromosomes in many crops such as rice (Cheng et al ., ) and Brassica (Pires & Xiong, ).…”
Section: Introductionmentioning
confidence: 99%
“…Sequences of ribosomal RNA genes and their spacers have been used profusely in an array of molecular phylogenetic (12, 13) and other approaches to plant evolution (14–16). Number, position and rDNA organization can also be used for, or at least complement comparative, evolutionary and systematic approaches (17–19), assuming that the karyotypes of closely related species are likely to be more similar than those of distant species (20, 21).…”
Section: Introductionmentioning
confidence: 99%